St. John Paul II’s Natural Law Legacy and International Human Rights Culture of Human Dignity – A Road to Universal Brotherhood and Peace - Ján Figel (Chrześcijaństwo-Świat-Polityka)
The text underscores the pivotal role of human dignity in shaping the notions justice, peace, and human rights in the 21st century. The author advocates a return to the core principles of key documents on this subject to counter the influence of various  ideologies and  totalitarian regimes. Highlighting secular and faith-based sources including the Universal Declaration of Human Rights and Vatican II Council Declaration, the text emphasizes human dignity as the meeting point for religious and secular humanists. It underscores the belief in the innate value of individuals and their equality in dignity, derived from the Judeo-Christian tradition. The three dimensions of Me, Thee, and We are explored, emphasizing personal uniqueness, respect for others, and societal responsibility. The text concludes by advocating for a culture of human dignity in politics, serving as the basis, purpose, and criterion for public policies, promoting equal dignity and fraternity for a just and unified society. The text discusses the historical evolution of the concept of human dignity in global constitutional history, highlighting its presence in contemporary constitutions and international declarations. It advocates the promotion of a culture of human dignity, encompassing gold and silver ethical principles. The conclusion emphasises the need for  a renewed commitment to a culture of human dignity in line with the legacy of John Paul II.